The art of managing various ocular defects in different clinical scenarios: A case series - Apurva Verma; Ramya Srinivasan; Kaushal Kishor Agrawal; Bhaskar Agarwal; Diksha Singh (Wolters Kluwer Medknow Publications, 2023)
The absence of eye and irradiation post-enucleation may result in problems like dryness of the eye sockets, itching and crusting. This may lead to poor prosthesis adaptation and a lack of patient acceptance of the prosthesis. To combat the most common problem of dryness, patients are advised artificial tears to use as teardrops or ocular prostheses along with a tear reservoir. This case series describes methods of fabricating ocular prosthesis indicated in different scenarios: the modified stock ocular and a custom-made ocular prosthesis when tearing secretion is enough in the eye socket and an ocular prosthesis with a tear reservoir in cases showing reduced tear secretion. A novel technique of fabricating hollow lightweight ocular prostheses having the sustained prolonged release of artificial tears has been described.